PEMANFAATAN QUIZIZZ BERBASIS INTERNET UNTUK MENINGKATKAN PENGUASAAN KOSAKATA BAHASA INGGRIS SISWA SEKOLAH DASAR - Helmi; Maneka Ciciana; Muhammad Rezeki (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
This study aims to determine the effectiveness of using internet-based Quizizz in improving elementary school students’ English vocabulary mastery. The research method used is an experimental design with a pretest-posttest approach. The subjects of this study were elementary school students divided into an experimental group and a control group. The instrument used was an English vocabulary test. Data analysis techniques employed statistical tests to examine differences in learning outcomes before and after the treatment. The results showed a significant improvement in students’ vocabulary mastery after using internet-based Quizizz compared to conventional teaching methods. Therefore, it can be concluded that the use of internet-based Quizizz is effective in improving elementary school students’ English vocabulary mastery